The Association between Depressive State and Maternal Cognitive Function in Postpartum Women - Mazor, Elad; Sheiner, Eyal; Wainstock, Tamar; Attias, Monic; Walfisch, Asnat (American Journal of Perinatology, 2019)
Objective Maternal amnesia is a transitional cognitive impairment occurring during pregnancy and the postpartum period. We evaluated the prevalence and extent of this suggested cognitive decline and the role of postpartum depression.Study Design A cross-sectional study was performed in women during the immediate postpartum period. Eligible women completed the Edinburgh Postnatal Depression Scale (EPDS). Cognitive function was assessed using an objective neurocognitive test (Symbol Digit Modalities Test, SDMT90, and SDMT4) and a subjective self-estimation questionnaire (Attention Function Index [AFI]).Results A total of 120 women completed the study questionnaires; 33.3% (40 women) exhibited signs of postpartum depression (EPDS ≥10). The subjective AFI test results correlated with the objective SDMT90 test results (r2 = 0.2, p = 0.039). Depressed mothers scored significantly lower in the subjective AFI test (67.69 ± 12.01 in the study vs. 79.05 ± 14.3 in the comparison group; p < 0.001) and nearly significantly lower in the objective SDMT test (p = 0.057). In the multi-variable model, maternal depression was independently associated with the subjective AFI score (β  = −13.7; 95% confidence interval [CI]: −19.1 to −8.2, p < 0.001) but not with the objective SDMT score (β = −3.48; 95% CI −8.3 to 1.3, p = 0.15), while controlling for maternal age, gestational age, and ethnicity.Conclusion Postpartum depression is common and appears to predominantly affect maternal self-assessment of cognitive ability, rather than a true cognitive impairment.
Keywords: postpartum depression; maternal amnesia; cognitive function; Edinburgh Postnatal Depression Scale